Carbon footprint assessment of Energy-Based devices in clinical and aesthetic dermatology - Karakoyun, Omer; Ayhan, Erhan; Aydin, Delal (Springer London Ltd, 2025)
Health care significantly contributes to global greenhouse gas emissions. Dermatology, particularly procedures involving energy-intensive devices such as lasers and light-based therapies, plays a notable role. To compare the per-session carbon footprint of commonly used aesthetic and clinical dermatologic devices and suggest strategies for sustainability. A descriptive life cycle assessment was conducted on 12 devices grouped as lasers, light-based tools, body-contouring systems, and alternative modalities. Device power data were sourced from manufacturers and literature; average session durations from clinical protocols. Energy use per session was calculated by multiplying power by session length and converted into CO2 equivalents using Turkey's national grid intensity (0.45 kg CO(2)e/kWh). High-energy lasers (IPL, Nd: YAG, Alexandrite, CO2) produced 0.30-0.70 kg CO(2)e per session. LED therapy, microdermabrasion, and sonophoresis emitted < 0.01 kg CO(2)e. Radiofrequency microneedling and EMS ranged between 0.10 and 0.70 kg CO(2)e. Diode lasers offered up to 50% reduction due to higher energy efficiency. Dermatologic devices vary widely in carbon output. Choosing low-emission tools, optimizing session times, and utilizing teledermatology can significantly reduce environmental impact. Integrating sustainability metrics into device selection may support greener dermatologic practices.
Keywords: Aesthetic dermatology; Clinical dermatology; Carbon footprint; Life cycle assessment; Sustainability